Bacterial Flora of the Intestines of Farm Raised Freshwater Fishes Catla catla, Labeo rohita and Ctenopharyngodon idella - A.A., Mohamed Hatha; Kuruvilla, Seena; Cheriyan, Synobia (Fishery Technology, 2025)
Bacterial flora associated with the intestines of farm raised freshwater fishes such as Labeo rohita, Catla catla and Ctenopharyngodon idella have been analysed. The mean population of total heterotrophic bacteria (THB) of the intestine of L. rohita was 3.2xl06 colony forming units (CFU) per gram and that of C. catla and C. idella were 4.79x10’’ and 1.13xl07 CFU respectively. Morphological and physiological grouping of the isolates revealed dominance of gram negative rod shaped bacteria capable of elaborating various hydrolytic enzymes such as amylase, lipase and gelatinase. Ureolytic forms were relatively few. Characterisation of the genera revealed the dominance of Aeromonas in the intestine of these fishes. Other genera encountered were Corynebacterium, Micrococcus, Alcaligenes, Vibrio, Moraxella, Bacillus, Lactobacillus, Acinetobacter, Flavobacterium and members of the family Enterobacteriaceae.